BATU NISAN LAMREH TIPE ‘PLANGPLENG’ - Dedy Satria (Balai Arkeologi Sumatera Utara, 2019)
Plangpleng type tombstone is a very distinctive shape. Sculpture style is the main characteristic of this type of tombstone. That makes it different from other tombstones in Lamreh. Forms of local and foreign motifs from different cultural backgrounds and belief systems. This is a character that reflects a 'mixed' society at the beginning of the development of Islam in Aceh Besar and Banda Aceh. This tombstone is a very important marker as the initial evidence of the presence of Muslim communities along the coast of Aceh Besar and Banda Aceh. As an art object, it has been a human work of the past, and is evidence of the culmination of the achievement of cultural development in an ancient society in Aceh Besar known as the 'Lamuri community’.